Self-Tolerance to the Murine Homologue of a Tyrosinase-Derived Melanoma Antigen: Implications for Tumor Immunotherapy - Colella, Teresa A. (The Rockefeller University Press, 2000)
The human tyrosinase-derived peptide YMDGTMSQV is presented on the surface of human histocompatibility leukocyte antigen (HLA)-A*0201(+) melanomas and has been suggested to be a tumor antigen despite the fact that tyrosinase is also expressed in melanocytes. To gain information about immunoreactivity and self-tolerance to this antigen, we established a model using the murine tyrosinase-derived homologue of this peptide FMDGTMSQV, together with transgenic mice expressing the HLA-A*0201 recombinant molecule AAD. The murine peptide was processed and presented by AAD similarly to its human counterpart. After immunization with recombinant vaccinia virus encoding murine tyrosinase, we detected a robust AAD-restricted cytotoxic T lymphocyte (CTL) response to FMDGTMSQV in AAD transgenic mice in which the entire tyrosinase gene had been deleted by a radiation-induced mutation. A residual response was observed in the AAD(+)tyrosinase(+) mice after activation under certain conditions. At least some of these residual CTLs in AAD(+)tyrosinase(+) mice were of high avidity and induced vitiligo upon adoptive transfer into AAD(+)tyrosinase(+) hosts. Collectively, these data suggest that FMDGTMSQV is naturally processed and presented in vivo, and that this presentation leads to substantial but incomplete self-tolerance. The relevance of this model to an understanding of the human immune response to tyrosinase is discussed.